1996
DOI: 10.1111/1523-1747.ep12345163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Subcellular Localization of Human Pmel 17/silver, a 100-kDa (Pre)Melanosomal Membrane Protein Associated With 5,6,-Dihydroxyindole-2-Carboxylic Acid (DHICA) Converting Activity

Abstract: Pmel 17 is preferentially expressed in pigment cells in a manner suggestive of involvement in melanin biosynthesis. The gene is identical to the silver (si) pigmentation locus in mice. We now produced a recombinant glutathione-S-transferase-human Pmel 17 infusion protein and raised polyclonal antibodies against it to confirm the ultrastructural location and presumed site of action predicted by the deduced primary structure of Pmel 17/silver, and to authenticate the specificity of the DHICA converting function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
66
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 30 publications
5
66
0
1
Order By: Relevance
“…1,[33][34] Similarly, the amyloid-like protein Pmel17/Silver/gp100 is capable of generating MN-like pigments in vitro or in vivo. 6,[35][36] Pmel17/Silver/gp100 is a melanocyte-specific protein within the matrix of the melanocytes upon which the MN pigment is deposited and organized. [37][38][39] It is worth noting that in the case of lignins, a plant-based polymeric substance derived from phenolic precursors, extracellular proteins containing so-called dirigent domains are involved in the deposition and organization of this pigment.…”
Section: Discussionmentioning
confidence: 99%
“…1,[33][34] Similarly, the amyloid-like protein Pmel17/Silver/gp100 is capable of generating MN-like pigments in vitro or in vivo. 6,[35][36] Pmel17/Silver/gp100 is a melanocyte-specific protein within the matrix of the melanocytes upon which the MN pigment is deposited and organized. [37][38][39] It is worth noting that in the case of lignins, a plant-based polymeric substance derived from phenolic precursors, extracellular proteins containing so-called dirigent domains are involved in the deposition and organization of this pigment.…”
Section: Discussionmentioning
confidence: 99%
“…The SILV protein appears to be necessary for the formation of the fibril matrix upon which melanin intermediates are deposited late in melanosome maturation (24). Other studies have shown that SILV may also participate in melanin biosynthesis by accelerating the conversion of 5,6-dihydroxyindole-2-carboxylic acid to melanin (34,35). The mutant phenotype of SILV in the human is unknown (28).…”
Section: Discussionmentioning
confidence: 99%
“…The amyloid sheets are critical determinants of the ellipsoid melanosome shape (12,13), which is required for proper melanosome motility into the apical processes of retinal pigment epithelial cells (14). The amyloid sheets have also been proposed to accelerate melanin polymerization (10,15,16), and organisms that lack PMEL or carry mutations in the PMEL gene are characterized by various degrees of hypopigmentation (13,(17)(18)(19)(20)(21). Because PMEL is synthesized in the endoplasmic reticulum (ER) as a type I transmembrane protein (22)(23)(24) but only initiates amyloid fibril formation within the lumen of endosomal membrane compartments (25)(26)(27), PMEL must navigate the secretory pathway from the ER to endosomes in a non-amyloid form.…”
mentioning
confidence: 99%